2008
DOI: 10.1063/1.2884699
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive gain and loss in midinfrared quantum cascade laser

Abstract: We report the measurements of dispersive gain (simultaneous coexistence of gain and losses on a single intersubband transition) in a quantum cascade laser. Broadband transmission spectra through the waveguide of a Lambda ~4.7 µm In0.53Ga0.47As/AlAs0.56Sb0.44/InP quantum cascade laser have been studied at a bias below laser threshold and at different temperatures. For a certain range of current, and at temperatures higher than about 150 K, the transmission spectra show clear dispersive gain/loss behavior with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…It has been recently demonstrated that a judicious combination of material and design parameters can lead to conduction bands with dispersion relation characterized with lower masses on top and heavier masses in lower subbands, thus allowing for local inversion in k-space and gain even though there is no global population inversion [11]. This study demonstrates that for similar effective masses, dispersive gain is recovered as expected [12,13], but for masses engineered to be sufficiently different there is a deviation from the dispersive shape.…”
Section: Introductionsupporting
confidence: 60%
“…It has been recently demonstrated that a judicious combination of material and design parameters can lead to conduction bands with dispersion relation characterized with lower masses on top and heavier masses in lower subbands, thus allowing for local inversion in k-space and gain even though there is no global population inversion [11]. This study demonstrates that for similar effective masses, dispersive gain is recovered as expected [12,13], but for masses engineered to be sufficiently different there is a deviation from the dispersive shape.…”
Section: Introductionsupporting
confidence: 60%
“…Furthermore it is interesting to notice that the dispersive gain expected for LWI 6,27 is found for similar effective masses. See Fig.…”
Section: ͑1͒mentioning
confidence: 97%
“…1(f), as recently observed in QCLs. 18,19 The same effect is common for superlattices where the total occupation f i (k) is identical for all Wannier-Stark states belonging to the lowest miniband. …”
Section: However This Only Holds Ifmentioning
confidence: 60%